Meta-Analisis Tentang Perilaku Koping Prevenstif dan Stres - Ahmad Muhammad Diponegoro; Syamsul Bachri Thalib (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2001)
This meta-analysis study focused on preventive coping and stress. Individual's study don't shows the  result that not always consistent and sometimes contradict each other.  So,  it is difficult to get the inclusive and integrative conclusion.The purpose of this study is to integrate the results of the study that varied about the relation between preventive coping and stres throughmeta-analysis procedure. The subject analysis contained 15 studies that consist 2816 sample size.  The result of this study reveals that (a) there is a relation between preventive coping and stres (rho= -0,383,  interval confidence 95% = -0,02 <P  < 0,74); (b) variance due  to sampling error=0,0043 (15,09%); (c) variance due to variation of reliability=  0,0012 (4. 18%).  This meta-analysis support concfution in the current literatur. The relation between preventive coping and stress became consis tence 1f we  consider the research artifact. either the amount of the sample, subject characteristics of research instruments. Key words: meta-anausls. penlaku koping  preventif, dan sires